Synthesis and Biocidal Effect of New Steroidal Heterocyclic Compounds - Omar Al-Footy, Khalid (Asian Journal of Chemistry, 2010)
The preparation of new steroidal heterocyclic compounds derived from testosterone and pregnenalone was described. The structure of new products was elucidated by spectroscopic techniques. The products were examined for their biocidal effect against bacteria and fungi and their results compared with standard antibiotics.